2017
DOI: 10.1007/978-1-4939-6981-4_24
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the Production of a Vaccine Against Argentinian Hemorrhagic Fever

Abstract: Argentinian hemorrhagic Fever (AHF) is a febrile, acute disease caused by Junín virus (JUNV), a member of the Arenaviridae. Different approaches to obtain an effective antigen to prevent AHF using complete live or inactivated virus, as well as molecular constructs, have reached diverse development stages. This chapter refers to JUNV live attenuated vaccine strain Candid #1, currently used in Argentina to prevent AHF. A general standardized protocol used at Instituto Nacional de Enfermedades Virales Humanas (Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Instituto Nacional de Enfermedades Virales Human (INEVH) in Pergamino was considered the best place for the production of vaccine boosters. The people working at the Salk Institute in Pennsylvania were trained in Goods manufacturing practices and quality control practices 66 . The vaccine produced in Argentina was tested on 946 human volunteers between 2005 and 2006.…”
Section: Diagnostics and Therapeutics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instituto Nacional de Enfermedades Virales Human (INEVH) in Pergamino was considered the best place for the production of vaccine boosters. The people working at the Salk Institute in Pennsylvania were trained in Goods manufacturing practices and quality control practices 66 . The vaccine produced in Argentina was tested on 946 human volunteers between 2005 and 2006.…”
Section: Diagnostics and Therapeutics Approachesmentioning
confidence: 99%
“…The people working at the Salk Institute in Pennsylvania were trained in Goods manufacturing practices and quality control practices. 66 The vaccine produced in Argentina was tested on 946 human volunteers between 2005 and 2006. Results showed that Candid#1 produced in Argentina was equally effective as Candid#1 produced in the U.S.…”
Section: Vaccinementioning
confidence: 99%